Exploring Identity Issues in Development Areas of Vernacular Rural Settlements: A Case Study of Behramkale, Türkiye - Boyacıoğlu, Didem; Göçer, Özgür; Karahan, Ebru Ergöz (Alanya Üniversitesi, 2023)
Sustainable rural development is a challenging issue, considering the pressure of change brought by the demands of globalisation and intensified tourism activities in rural vernacular settlements. While studies in this field often focus on historical centres, research on the distinctive urban and architectural identity of “village development areas” in rural vernacular settlements remains scarce. To address this gap in the literature, a field study was conducted in the vernacular rural settlement of Behramkale, located in the Northern Aegean region of Türkiye. The study explored the continuity of architectural and urban identity and its significance. The research involved a qualitative assessment of primary data obtained through architectural surveys and archival documents collected in 2017 and 2021. Data analysis not only focused on static features of place identity but included dynamic and perceptual features of place identity. Planning policy inadequacies and the implications of top-down decisions on vernacular rural Türkiye are discussed. The key finding from the study highlights the necessity for a more participatory and site-specific approach to preserving vernacular rural heritage’s urban and architectural identity for sustainable development. In this regard, the paper proposes that an identity-based and people-centred approach should be integrated into the policies for the development areas of vernacular rural settlements. This integration aims to preserve the local architectural identity and promote a belongingness community among residents.